Aortic valve replacement rates in Australia from 2004 to 2019. Issue 4 (20th August 2022) - Bamford, Paul; Said, Christian; Al‐Omary, Mohammed S.; Bhagwandeen, Rohan; Boyle, Andrew
Abstract: Background: Several surgical and percutaneous treatments are available for patients with aortic valve disease. Aim: To establish whether trends in aortic valve replacements (AVR) in Australia reflect recent evidence. Methods: Using the Australian Institute of Health and Welfare data, this study calculated all AVR and balloon aortic valvuloplasty (BAV) procedures conducted in all Australian hospitals from 2004 to 2019. Linear regression analysis was performed to determine whether age‐adjusted rates had changed over the study period. Results: There were 80 883 AVR performed. Of these, 66% were men and 64% were aged >70 years. Absolute rates of AVR increased from 3631 to 7277 with a significant 22% age‐adjusted rise seen (1.9% increase per year (+0.26 per 100 000 per year; 95% confidence interval 0.19–0.34); P < 0.001). This trend was more pronounced in men than women and in those aged >80 years (+0.23 per 100 000 per year; P < 0.001). Proportion of mechanical AVR implanted fell from 38.4% to 8.6% ( P < 0.001). A total of 2683 transcatheter aortic valve implantation (TAVI) procedures was performed in 2019, representing a 52% annual increase from 2014. BAV increased from 66 procedures in 2004 to 862 in 2019. Conclusion: Rates of AVR have increased significantly over the past 16 years, particularly in the elderly. Despite international guideline recommendations, fewer mechanical AVR are being used in younger cohorts. The uptake in TAVI rates might reflect evidence that suggests it is a safe alternative, at least in the medium term. BAV has also seen a resurgence during this time period.